Assistance for Halal Based Tourism Object Management on the Banks of the Kampar River - Tuti Andriani; Gusma Afriani; Nelvia Ibrahim; Yuriyan Dinata; Rahmat Yoza Mandela (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Management of natural and culinary tourism along the banks of the Kampar River still suffers from low basic infrastructure, weak service quality, and a lack of understanding of halal tourism standards, making the destination unprepared for competition. This community service program aims to improve the capacity of managers to implement halal tourism principles through managerial mentoring, facility development, and community-based human resource development. The program uses an Asset-Based Community Development (ABCD) approach with the stages of Discovery, Dream, Design, and Destiny. Data were collected through facility condition observations, in-depth interviews with managers, focus group discussions (FGDs) to formulate destination needs and visions, and community asset mapping. Analysis was conducted using descriptive qualitative methods, synthesizing the gap between existing conditions and halal tourism standards. The program resulted in standard operating procedures (SOPs) for halal tourism, increased understanding of halal certification, improved hygiene and prayer facilities, enhanced digital skills, and the establishment of tourism groups (Pokdarwis) and tourism police as sustainability institutions. These findings indicate a shift from spontaneous management to structured governance. Strengthening local regulations, ongoing monitoring, and further research based on impact evaluation are needed to measure improvements in service quality and destination competitiveness.